Gut Microbiota: Its Potential Roles in Pancreatic Cancer - Li, Quanxiao; Jin, Meng; Liu, Yahui; Jin, Limin (Frontiers in Cellular and Infection Microbiology, 2020)
Pancreatic cancer is considered a lethal disease with a low survival rate due to its late-stage diagnosis, few opportunities for resection and lack of effective therapeutic strategies. Multiple, highly complex effects of gut microbiota on pancreatic cancer have been recognized as potential strategies for targeting tumorigenesis, development and treatment in recent decades; some of the treatments include antibiotics, probiotics and fecal microbiota transplantation. Several bacterial species are associated with carcinogenesis of the pancreas, while some bacterial metabolites contribute to tumor-associated low-grade inflammation and immune responses via several proinflammatory factors and signaling pathways. Given the limited evidence on the interplay between gut microbiota and pancreatic cancer, risk factors associated with pancreatic cancer, such as diabetes, chronic pancreatitis and obesity, should also be taken into consideration. In terms of treatment of pancreatic cancer, gut microbiota has exhibited multiple effects on both traditional chemotherapy and the recently successful immunotherapy. Therefore, in this review, we summarize the latest developments and advancements in gut microbiota in relation to pancreatic cancer to elucidate its potential value.